Aspects of knowledge, attitudes and practices of medical practitioners on obesity and weight management in three urban centres in Kenya - Ojwang, Alice AChieng (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MNutr (Interdisciplinarty Health Sciences. Human Nutrition))--University of Stellenbosch, 2005.